Embedded catalyst as well as preparation method and application thereof
By embedding Pt and coactive component M in the pure silicon molecular sieve support, the catalyst is synthesized by using the precursor-post-hydrothermal crystallization method, the problems of high energy consumption and environmental protection in the prior art are solved, the activity and stability of the catalyst are improved, and low energy consumption and environmentally friendly ethylene production is achieved.
Patent Information
- Application Number
- CN202311199418.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-18
AI Technical Summary
The existing ethylene production technology has high energy consumption and environmental protection problems, and the platinum-based catalyst uses flammable and explosive ethylenediamine and ammonia-containing and fluorine-containing substances during the preparation process.
A pure silicon molecular sieve without Al is used as a support, Pt and coactive component M are embedded, and metal embedded molecular sieve catalysts are synthesized by precursor-post-hydrothermal crystallization, which avoids the sintering and migration of metal particles and reduces environmental pollution during the preparation process.
It improves the activity, selectivity and stability of the catalyst, achieves low energy consumption and environmentally friendly ethylene production, and avoids the use of flammable, explosive and environmentally harmful substances.
Smart Images

Figure CN119633878A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to an embedded catalyst and a preparation method and application thereof. Background Art
[0002] Ethylene is an important raw material for the production of a large number of petrochemical products including fibers, rubber, plastics, coatings, pesticides, electronic equipment, etc. The ethylene industry is the core of the petrochemical industry, and its output is one of the important indicators of the development level of a country's petrochemical industry. It is estimated that by 2035, human demand for ethylene will reach 25 billion tons (X. Li et al. J. Energy Chem. 2020, 51 14-20). Existing technologies for ethylene production include ethane pyrolysis, steam cracking of naphtha, and fluid catalytic cracking of naphtha. For ethane steam cracking, the required temperature is usually >1000°C, and the energy consumption is high. For naphtha steam cracking and fluid catalytic cracking, not only a high temperature of usually >800°C is required, but also the raw materials are derived from crude oil. On the one hand, crude oil prices continue to rise and oil resources are gradually exhausted; on the other hand, in recent years, my country has vigorously promoted green development and promoted efficient production paths for industrial raw materials in non-petrochemical routes. Therefore, since the existing ethylene production path has the characteristics of strong heat absorption and high energy consumption, it is necessary to develop a low-energy and relatively environmentally friendly production path. With the large-scale exploitation of shale gas, the supply of ethane has soared by more than 15 times (L. Liu et al. Chem 2022, 9, 1-13). Using ethane, the second largest component (>10%) in shale gas, as raw gas, and using the ethane dehydrogenation pathway (EDH) to produce ethylene has the advantages of environmental protection, high efficiency, and low energy consumption. It is an alternative route with great market prospects and has become one of the research hotspots in recent years.
[0003] CN110871106A discloses the use of solid phase method and liquid phase method to synthesize metal embedded HZSM-5 molecular sieve catalyst, which has excellent ethane and propane conversion stability, but the crystallization time during the molecular sieve synthesis is relatively long (48-96h), and NH3·H2O and NH4F substances are added during the synthesis process, which is not conducive to environmental protection requirements.
[0004] CN110479353A discloses a catalyst that encapsulates clusters of Pt and Zn into pure silicon molecular sieves, which exhibits excellent PDH performance. However, in the catalyst preparation process, ethylenediamine is required to form a complex with a metal salt solution as a protective ligand, and ethylenediamine is at risk of causing combustion and explosion when exposed to fire or high heat. In addition, the crystallization time during the molecular sieve synthesis process is relatively long (72h).
[0005] It can be seen that the Pt-based catalyst with molecular sieve as carrier and metal embedded in the molecular sieve framework has excellent alkane dehydrogenation performance, but there are still some problems: the catalyst efficiency such as the selectivity for the target product needs to be improved, the use of ammonia and fluorine-containing substances that are harmful to the environment should be avoided, and the use of flammable and explosive ethylenediamine should be avoided. It is expected that the crystallization time in the molecular sieve synthesis process can be further reduced. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems existing in the prior art, such as the metal particles in the platinum-based catalyst are easy to sinter, the catalyst is easy to be deactivated by carbon deposition, the catalytic efficiency needs to be improved, and the preparation process contains environmentally unfriendly substances such as ammonia and fluorine and / or the flammable and explosive dangerous substance ethylenediamine, and to provide an embedded catalyst and its preparation method and application. The embedded catalyst of the present invention has better selectivity and conversion rate than the supported catalyst, and the preparation method of the present invention is efficient, safe and environmentally friendly.
[0007] In order to achieve the above-mentioned purpose, the present invention provides an embedded catalyst on the one hand, which includes a carrier and a main active component Pt and an optional auxiliary active component M embedded in the carrier; wherein the carrier is a pure silicon molecular sieve; and the auxiliary active component M is selected from one or more of Zn, Ga, Sn, In and K.
[0008] A second aspect of the present invention provides a method for preparing an embedded catalyst, the preparation method comprising:
[0009] (1) impregnating a silicon source with a solution of a first metal salt, and subjecting the mixture to vacuum evacuation, drying and calcination to obtain a first catalyst precursor;
[0010] (2) impregnating the first catalyst precursor with a solution of a second metal salt, and subjecting the mixture to vacuum evacuation, drying and calcination to obtain a second catalyst precursor;
[0011] (3) hydrothermally crystallizing the second catalyst precursor in the presence of deionized water and a template, filtering, drying and calcining to obtain a catalyst precursor;
[0012] (4) reducing the catalyst precursor in a reducing gas atmosphere to obtain an embedded catalyst.
[0013] The third aspect of the present invention provides the use of the embedded catalyst provided in the first aspect or the embedded catalyst prepared by the preparation method provided in the second aspect in ethane dehydrogenation.
[0014] A fourth aspect of the present invention provides a method for dehydrogenating ethane, the method comprising: contacting a gas containing ethane with a catalyst to react, to dehydrogenate ethane;
[0015] Wherein, the catalyst is selected from at least one of the embedded catalysts provided in the first aspect or the embedded catalysts prepared by the preparation method provided in the second aspect.
[0016] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0017] (1) The embedded catalyst of the present invention uses pure silicon molecular sieve without Al as a carrier, and the metal active components (Pt and M) are embedded in the skeleton structure of the carrier, which can avoid the migration and Ostwald ripening of metal particles and then aggregation, causing metal agglomeration and then sintering; it is used for catalytic dehydrogenation of ethane to produce ethylene, which can improve the activity, selectivity and stability of the catalyst.
[0018] (2) Using pure silicon molecular sieve as a carrier, a metal-embedded molecular sieve catalyst was synthesized by a pre-polymer-post-hydrothermal crystallization method. This preparation method can obtain a highly crystalline molecular sieve in a relatively short crystallization time, with a twin hexagonal prism morphology. In addition, no ammonia- or fluorine-containing substances need to be added during the preparation process, which is environmentally friendly. In addition, no flammable and explosive ethylenediamine needs to be added as a protective ligand during the preparation process, which greatly improves safety.
[0019] (3) The method of the present invention allows the metal substance to be embedded into the skeleton structure of the molecular sieve, thereby stabilizing the metal substance and avoiding its sintering and migration. Therefore, the catalyst prepared by this method has high ethane catalytic dehydrogenation (EDH) activity (the ethane conversion rate reaches the highest thermodynamic equilibrium value that can be achieved under this reaction condition) and high stability (the deactivation rate is only 0.00113h -1 ); at the same time, since pure silicon molecular sieve without Al is used as the carrier, side reactions such as deep dehydrogenation promoted by the B acid site on the Al site are avoided, so that the synthesized catalyst has excellent anti-carbon deposition performance and achieves high ethylene selectivity (≥95%); at the same time, no ammonia-containing or fluorine-containing substances are added during the preparation process; no inflammable and explosive ethylenediamine is used; the catalyst raw materials are cheap and easy to obtain, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 X-ray diffraction patterns of the catalysts obtained in Examples 2, 4 and 6;
[0021] Figure 2a This is the SEM image of the ZnPt@S-1 catalyst obtained in Example 4;
[0022] Figure 2b for Figure 2a A partial enlarged view of
[0023] Figure 3 HRTEM image of the ZnPt@S-1 catalyst obtained in Example 4;
[0024] Figure 4a This is a particle size distribution diagram of the metal particles in the ZnPt@S-1 catalyst obtained in Example 4 before the EDH reaction;
[0025] Figure 4b This is the particle size distribution diagram of the metal particles in the ZnPt@S-1 catalyst obtained in Example 4 after EDH reaction for 30 hours;
[0026] Figure 5 The graph showing the change of ethane equilibrium conversion rate with temperature at 0.3 bar ethane partial pressure calculated using HSC 6.0 software. DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] The first aspect of the present invention provides an embedded catalyst, which includes a carrier and a main active component Pt and an optional auxiliary active component M embedded in the carrier; wherein the carrier is a pure silicon molecular sieve; and the auxiliary active component M is selected from one or more of Zn, Ga, Sn, In and K.
[0029] In the present invention, the catalyst is a molecular sieve catalyst, and the main active component Pt and the auxiliary active component M are embedded in the pure silicon molecular sieve, which means that the main active component Pt and the auxiliary active component M are wrapped in the framework of the pure silicon molecular sieve.
[0030] The embedded catalyst of the present invention uses pure silicon molecular sieve without Al as a carrier, which can avoid the negative effects of deep dehydrogenation carbon deposition and low hydrothermal stability caused by the B acid site on the Al site; by embedding the metal substance into the molecular sieve skeleton structure, the migration and Ostwald ripening of metal particles and then aggregation can be avoided, causing metal agglomeration and then sintering; the introduction of a second metal such as Zn, Ga, Sn, In and alkali metal K as an auxiliary agent can improve the dispersion of Pt, reduce the particle size, and further improve the activity, stability and target product selectivity of the catalyst.
[0031] In some embodiments of the present invention, the molar ratio of the auxiliary active component M to the main active component Pt is 0.2-9:1, preferably 0.3-3.6:1.
[0032] In some embodiments of the present invention, in the embedded catalyst, based on the total weight of the embedded catalyst, the content of the first metal M1 is 0.5-1.5wt%, preferably 0.8-1.2wt%; the content of the second metal M2 is 0-1.5wt%, preferably 0.7-1.2wt%.
[0033] In the present invention, part of the auxiliary active component M and the main active component Pt exist in the form of an alloy, and the final catalyst may contain Pt, metal M and an alloy; the particle size of the alloy is 2-6nm, preferably 3-4nm, for example, the particle size of the metal particles in the PtZn bimetallic catalyst is about 3.9nm.
[0034] In some embodiments of the present invention, the pure silicon molecular sieve is selected from Silicalite-1 molecular sieve or β molecular sieve.
[0035] In the present invention, Silicalite-1 molecular sieve is referred to as S-1 molecular sieve.
[0036] In some embodiments of the present invention, the pore size of the pure silicon molecular sieve is 4.5-5.5 angstroms, and the specific surface area is not less than 300 m 2 / g.
[0037] In some embodiments of the present invention, the pure silicon molecular sieve has a regular hexagonal prism shape and a twinned crystal structure.
[0038] The twin crystal structures of the pure silicon molecular sieve in the present invention are uniform in size.
[0039] A second aspect of the present invention provides a method for preparing an embedded catalyst, the preparation method comprising:
[0040] (1) impregnating a silicon source with a solution of a first metal salt, and subjecting the mixture to vacuum evacuation, drying and calcination to obtain a first catalyst precursor;
[0041] (2) impregnating the first catalyst precursor with a solution of a second metal salt, and subjecting the mixture to vacuum evacuation, drying and calcination to obtain a second catalyst precursor;
[0042] (3) hydrothermally crystallizing the second catalyst precursor in the presence of deionized water and a template, filtering, drying and calcining to obtain a catalyst precursor;
[0043] (4) reducing the catalyst precursor in a reducing gas atmosphere to obtain an embedded catalyst.
[0044] In the present invention, between step (2) and step (3), the method further comprises: grinding the second catalyst precursor, preferably grinding it to a size of less than 100 meshes, and then performing hydrothermal crystallization.
[0045] According to the present invention, a metal-embedded molecular sieve catalyst is synthesized by a pre-hydrothermal crystallization method using pure silicon molecular sieve as a carrier. The preparation method can obtain a molecular sieve with high crystallinity in a relatively short crystallization time, and the morphology of the zeolite is twinned hexagonal prisms. In addition, no ammonia-containing or fluorine-containing substances need to be added during the preparation process, and the catalyst is environmentally friendly. In addition, no inflammable and explosive ethylenediamine needs to be added as a protective ligand during the preparation process, and the safety is greatly improved.
[0046] The method of the present invention uses a metal / SiO2 precursor as a Si source, and dissolves the Si source and grows a pure silicon molecular sieve in situ through the structural guidance of a template agent during the hydrothermal crystallization process, so that the metal substance is embedded in the skeleton structure of the molecular sieve, thereby stabilizing the metal substance and avoiding its sintering and migration. Therefore, the catalyst prepared by the method has high ethane catalytic dehydrogenation (EDH) activity (the ethane conversion rate reaches the highest thermodynamic equilibrium value that can be achieved under the reaction conditions) and high stability (the deactivation rate is only 0.00113h -1 ); can be used to efficiently catalyze EDH.
[0047] Since the method of the present invention uses pure silicon molecular sieve without Al as a carrier, side reactions such as deep dehydrogenation promoted by the B acid site on the Al site are avoided, so that the synthesized catalyst has excellent anti-carbon deposition performance and achieves high ethylene selectivity (≥95%); at the same time, no ammonia-containing or fluorine-containing substances are added during the preparation process; no inflammable and explosive ethylenediamine is used; the catalyst raw material is cheap and easy to obtain, and the cost is low.
[0048] The method of the present invention sequentially loads the first metal salt and the second metal salt on the Si source in a sequential impregnation manner, and then in the process of hydrothermal crystallization, the metal M and the metal Pt are encapsulated in the framework of the pure silicon molecular sieve, and the metal M partially modifies the metal Pt, changing the size and electronic properties of Pt.
[0049] In some embodiments of the present invention, the first metal salt is selected from one or more of zinc acetate dihydrate, zinc nitrate, tin nitrate, tin chloride, gallium nitrate, indium nitrate, potassium nitrate and potassium hydroxide.
[0050] In some embodiments of the present invention, the second metal salt is selected from one or more of dinitrodiammineplatinum, chloroplatinic acid and tetraammineplatinum nitrate.
[0051] In some embodiments of the present invention, the mass ratio of the first metal salt to the silicon source is 0-1.5:1.
[0052] In the present invention, when the first metal salt is 0, that is, the first metal salt is not impregnated, the method does not include step (1), that is, directly impregnating the silicon source with a solution of the second metal salt, and obtaining a catalyst precursor through vacuum pumping, drying and calcination; and then performing steps (3) and (4).
[0053] In some embodiments of the present invention, the mass ratio of the second metal salt to the silicon source is 0.5-1.5:1.
[0054] In some embodiments of the present invention, the molar ratio of deionized water, template agent and silicon source is 20-60:0.15-0.6:1.
[0055] In some embodiments of the present invention, the drying conditions include: drying temperature of 80-160° C., and drying time of 8-24 h.
[0056] In some embodiments of the present invention, the calcination conditions include: calcination temperature of 350-600° C., and calcination time of 1-8 h.
[0057] In some embodiments of the present invention, the hydrothermal crystallization conditions include: crystallization temperature of 170-200° C., crystallization time of 8-96 h, preferably 8-60 h, and more preferably 10-40 h.
[0058] In some embodiments of the present invention, the reduction conditions include: reduction temperature 350-600° C., and reduction time 1-3 h.
[0059] In some embodiments of the present invention, the reducing gas is an inert gas containing hydrogen, wherein the volume content of hydrogen is 5-95%, and the gas velocity of the reducing gas is 20-60 mL / min.
[0060] In the present invention, the structure of the first catalyst precursor is a first metal / SiO2 precursor, wherein “ / ” represents the first metal particles loaded on the SiO2 surface; the structure of the second catalyst precursor is a bimetallic / SiO2 precursor, wherein “ / ” represents the bimetallic particles loaded on the SiO2 surface.
[0061] In some embodiments of the present invention, the silicon source is selected from one or more of crystalline silica, amorphous silica and silica gel colloid.
[0062] In some embodiments of the present invention, the template is selected from tetrapropylammonium hydroxide (TPAOH) or propylammonium bromide or tetraethylammonium hydroxide.
[0063] The third aspect of the present invention provides the use of the embedded catalyst provided in the first aspect or the embedded catalyst prepared by the preparation method provided in the second aspect in ethane dehydrogenation.
[0064] The embedded catalyst of the present invention is used for ethane dehydrogenation to ensure stable operation of the reaction and rich production of ethylene.
[0065] A fourth aspect of the present invention provides a method for dehydrogenating ethane, the method comprising: contacting a gas containing ethane with a catalyst to react, to dehydrogenate ethane;
[0066] Wherein, the catalyst is selected from at least one of the embedded catalysts provided in the first aspect or the embedded catalysts prepared by the preparation method provided in the second aspect.
[0067] In some embodiments of the present invention, the flow rate of the ethane-containing gas is 5-50 mL / min.
[0068] In some embodiments of the present invention, the volume content of ethane in the ethane-containing gas is 5-90%.
[0069] In some embodiments of the present invention, the reaction conditions are: reaction temperature is 450-650° C.; reaction pressure is 0.1-0.3 MPa.
[0070] The catalyst of the present invention uses pure silicon molecular sieve S-1 as a carrier, and synthesizes a metal-embedded S-1 molecular sieve catalyst for high-efficiency catalysis of EDH by a pre-solid-post hydrothermal synthesis method.
[0071] According to a particularly preferred embodiment of the present invention, the specific method is as follows:
[0072] 1) Preparation of single metal precursor:
[0073] The single metal precursor is prepared by the equal volume impregnation method. Weigh a certain amount of metal reagent and mix it with an appropriate amount of deionized water, and load the metal salt solution on high-purity silica gel (SiO2, Si source) by equal volume impregnation. Then vacuum evacuate, dry and calcine. The resulting single metal / SiO2 precursor. Among them, " / " means that the metal particles are loaded on the SiO2 surface.
[0074] 2) Preparation of bimetallic precursors:
[0075] The bimetallic precursor is prepared by a step-by-step equal volume impregnation method. First, prepare a monometallic precursor according to step 1). Weigh a certain amount of the second metal and mix it with an appropriate amount of deionized water, and load the second metal salt solution on the prepared monometallic precursor by equal volume impregnation. After that, it is also subjected to vacuum evacuation, drying, and calcination. The resulting product is a bimetallic / SiO2 precursor. Among them, " / " means that the metal particles are loaded on the SiO2 surface.
[0076] 3) Hydrothermal synthesis:
[0077] Tetrapropylammonium hydroxide (TPAOH) is used as a template for the structure-directed synthesis of molecular sieves. After fully grinding the monometallic or bimetallic Si source precursor prepared by step 1 or 2, Si source, deionized water and TPAOH are added to the polytetrafluoroethylene liner in a certain molar ratio, and stirred at room temperature. Then, the liner is loaded with a stainless steel sleeve to crystallize and synthesize the molecular sieve.
[0078] 4) Filtration, washing, drying and roasting:
[0079] After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried and calcined to burn off the template. The resulting catalyst is metal@S-1. Here, "@" means that the metal particles are embedded in the S-1 molecular sieve framework.
[0080] 5) Tableting and granulation.
[0081] 6) Restore.
[0082] The catalyst prepared by the above method can be reduced during preparation or before use. In order to ensure the activity of the catalyst, it is preferred to reduce the catalyst before use.
[0083] The present invention will be described in detail below by way of examples. In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0084] Example 1
[0085] 1) Weigh 0.0102 g of zinc acetate dihydrate, dissolve it in deionized water, and stir it to fully dissolve it to obtain a white zinc salt solution; weigh 3 g of high-purity silica gel, drop the zinc salt solution on the high-purity silica gel, stir it to fully impregnate it, then vacuum evacuate for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a Zn / SiO2 precursor;
[0086] 2) Weigh 1.4687 g of dinitrosodiammine platinum nitrate solution, dissolve it in deionized water, stir to fully dissolve it, and obtain a colorless, clear and transparent platinum salt solution; add the platinum salt solution dropwise to the Zn / SiO2 precursor obtained in step 1), stir to fully impregnate it, then vacuum pump for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a ZnPt / SiO2 precursor;
[0087] 3) Weigh 20.0591g of deionized water, grind the ZnPt / SiO2 precursor obtained in step 2) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir thoroughly at room temperature until the mixture is uniform. Then transfer the mixture into a steel jacket and crystallize at 180°C for 40h.
[0088] 4) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0089] 5) 0.3 g of catalyst precursor was loaded into a quartz tube, and first reduced with H2, with specific reduction conditions of 550°C, gas velocity of 10000 mL / (g·h), and reduction time of 2 h. After the reduction, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to raw gas C2H6 / N2=3 / 7, with a gas velocity of 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, with a reaction pressure of 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0090] Example 2
[0091] 1) Weigh 0.0306 g of zinc acetate dihydrate, dissolve it in deionized water, and stir it to fully dissolve it to obtain a white zinc salt solution; weigh 3 g of high-purity silica gel, drop the zinc salt solution on the high-purity silica gel, stir it to fully impregnate it, then vacuum evacuate for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a Zn / SiO2 precursor;
[0092] 2) Weigh 1.4717 g of dinitrosodiammineplatinum nitrate solution, dissolve it in deionized water, stir to fully dissolve it, and obtain a colorless, clear and transparent platinum salt solution; add the platinum salt solution dropwise to the Zn / SiO2 precursor obtained in step 1), stir to fully impregnate it, then vacuum pump for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a ZnPt / SiO2 precursor;
[0093] 3) Weigh 20.0591g of deionized water, grind the ZnPt / SiO2 precursor obtained in step 2) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir thoroughly at room temperature until the mixture is uniform. Then transfer the mixture into a steel jacket and crystallize at 180°C for 40h.
[0094] 4) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0095] 5) 0.3 g of catalyst precursor was loaded into a quartz tube, and first reduced with H2, with specific reduction conditions of 550°C, gas velocity of 10000 mL / (g·h), and reduction time of 2 h. After the reduction, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to raw gas C2H6 / N2=3 / 7, with a gas velocity of 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, with a reaction pressure of 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0096] Example 3
[0097] 1) Weigh 0.0511 g of zinc acetate dihydrate, dissolve it in deionized water, and stir it to fully dissolve it to obtain a white zinc salt solution; weigh 3 g of high-purity silica gel, drop the zinc salt solution on the high-purity silica gel, stir it to fully impregnate it, then vacuum evacuate for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a Zn / SiO2 precursor;
[0098] 2) Weigh 1.4747 g of dinitrosodiammine platinum nitrate solution, dissolve it in deionized water, stir to fully dissolve it, and obtain a colorless, clear and transparent platinum salt solution; add the platinum salt solution dropwise to the Zn / SiO2 precursor obtained in step 1), stir to fully impregnate it, then vacuum pump for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a ZnPt / SiO2 precursor;
[0099] 3) Weigh 20.0591g of deionized water, grind the ZnPt / SiO2 precursor obtained in step 2) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir thoroughly at room temperature until the mixture is uniform. Then transfer the mixture into a steel jacket and crystallize at 180°C for 40h.
[0100] 4) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0101] 5) 0.3 g of catalyst precursor was loaded into a quartz tube, and first reduced with H2, with specific reduction conditions of 550°C, gas velocity of 10000 mL / (g·h), and reduction time of 2 h. After the reduction, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to raw gas C2H6 / N2=3 / 7, with a gas velocity of 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, with a reaction pressure of 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0102] Example 4
[0103] 1) Weigh 0.0717 g of zinc acetate dihydrate, dissolve it in deionized water, and stir it to fully dissolve it to obtain a white zinc salt solution; weigh 3 g of high-purity silica gel, drop the zinc salt solution on the high-purity silica gel, stir it to fully impregnate it, then vacuum evacuate for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a Zn / SiO2 precursor;
[0104] 2) Weigh 1.4777 g of dinitrosodiammineplatinum nitrate solution, dissolve it in deionized water, stir to fully dissolve it, and obtain a colorless, clear and transparent platinum salt solution; add the platinum salt solution dropwise to the Zn / SiO2 precursor obtained in step 1), stir to fully impregnate it, then vacuum pump for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a ZnPt / SiO2 precursor;
[0105] 3) Weigh 20.0591g of deionized water, grind the ZnPt / SiO2 precursor obtained in step 2) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir thoroughly at room temperature until the mixture is uniform. Then transfer the mixture into a steel jacket and crystallize at 180°C for 40h.
[0106] 4) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0107] 5) 0.3 g of catalyst precursor was loaded into a quartz tube, and first reduced with H2, with specific reduction conditions of 550°C, gas velocity of 10000 mL / (g·h), and reduction time of 2 h. After the reduction, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to raw gas C2H6 / N2=3 / 7, with a gas velocity of 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, with a reaction pressure of 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0108] Example 5
[0109] 1) Weigh 0.1028 g of zinc acetate dihydrate, dissolve it in deionized water, and stir it to fully dissolve it to obtain a white zinc salt solution; weigh 3 g of high-purity silica gel, drop the zinc salt solution on the high-purity silica gel, stir it to fully impregnate it, then vacuum evacuate for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a Zn / SiO2 precursor;
[0110] 2) Weigh 1.4822 g of dinitrosodiammineplatinum nitrate solution, dissolve it in deionized water, stir to fully dissolve it, and obtain a colorless, clear and transparent platinum salt solution; add the platinum salt solution dropwise to the Zn / SiO2 precursor obtained in step 1), stir to fully impregnate it, then vacuum pump for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a ZnPt / SiO2 precursor;
[0111] 3) Weigh 20.0591g of deionized water, grind the ZnPt / SiO2 precursor obtained in step 2) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir thoroughly at room temperature until the mixture is uniform. Then transfer the mixture into a steel jacket and crystallize at 180°C for 40h.
[0112] 4) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0113] 5) 0.3 g of catalyst precursor was loaded into a quartz tube, and first reduced with H2, with specific reduction conditions of 550°C, gas velocity of 10000 mL / (g·h), and reduction time of 2 h. After the reduction, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to raw gas C2H6 / N2=3 / 7, with a gas velocity of 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, with a reaction pressure of 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0114] Example 6
[0115] 1) Weigh 0.1236 g of zinc acetate dihydrate, dissolve it in deionized water, and stir it to fully dissolve it to obtain a white zinc salt solution; weigh 3 g of high-purity silica gel, drop the zinc salt solution on the high-purity silica gel, stir it to fully impregnate it, then vacuum evacuate for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a Zn / SiO2 precursor;
[0116] 2) Weigh 1.4853 g of dinitrosodiammineplatinum nitrate solution, dissolve it in deionized water, stir to fully dissolve it, and obtain a colorless, clear and transparent platinum salt solution; add the platinum salt solution dropwise to the Zn / SiO2 precursor obtained in step 1), stir to fully impregnate it, then vacuum pump for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a ZnPt / SiO2 precursor;
[0117] 3) Weigh 20.0591g of deionized water, grind the ZnPt / SiO2 precursor obtained in step 2) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir thoroughly at room temperature until the mixture is uniform. Then transfer the mixture into a steel jacket and crystallize at 180°C for 40h.
[0118] 4) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0119] 5) 0.3 g of catalyst precursor was loaded into a quartz tube, and first reduced with H2, with specific reduction conditions of 550°C, gas velocity of 10000 mL / (g·h), and reduction time of 2 h. After the reduction, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to raw gas C2H6 / N2=3 / 7, with a gas velocity of 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, with a reaction pressure of 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0120] Example 7
[0121] 1) Weigh 0.0717 g of zinc acetate dihydrate, dissolve it in deionized water, and stir it to fully dissolve it to obtain a white zinc salt solution; weigh 3 g of high-purity silica gel, drop the zinc salt solution on the high-purity silica gel, stir it to fully impregnate it, then vacuum evacuate for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a Zn / SiO2 precursor;
[0122] 2) Weigh 0.0641 g of chloroplatinic acid, dissolve it in deionized water, stir to fully dissolve it, and obtain a yellow, clear and transparent platinum salt solution; add the platinum salt solution dropwise to the Zn / SiO2 precursor obtained in step 1), stir to fully impregnate it, then vacuum pump for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a ZnPt / SiO2 precursor;
[0123] 3) Weigh 20.0591g of deionized water, grind the ZnPt / SiO2 precursor obtained in step 2) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir thoroughly at room temperature until the mixture is uniform. Then transfer the mixture into a steel jacket and crystallize at 180°C for 40h.
[0124] 4) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0125] 5) 0.3 g of catalyst precursor was loaded into a quartz tube, and first reduced with H2, with specific reduction conditions of 550°C, gas velocity of 10000 mL / (g·h), and reduction time of 2 h. After the reduction, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to raw gas C2H6 / N2=3 / 7, with a gas velocity of 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, with a reaction pressure of 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0126] Example 8
[0127] 1) Weigh 0.0717 g of zinc acetate dihydrate, dissolve it in deionized water, and stir it to fully dissolve it to obtain a white zinc salt solution; weigh 3 g of high-purity silica gel, drop the zinc salt solution on the high-purity silica gel, stir it to fully impregnate it, then vacuum evacuate for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a Zn / SiO2 precursor;
[0128] 2) Weigh 0.0641 g of chloroplatinic acid, dissolve it in deionized water, stir to fully dissolve it, and obtain a yellow, clear and transparent platinum salt solution; add the platinum salt solution dropwise to the Zn / SiO2 precursor obtained in step 1), stir to fully impregnate it, then vacuum pump for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a ZnPt / SiO2 precursor;
[0129] 3) Weigh 20.0591g of deionized water, grind the ZnPt / SiO2 precursor obtained in step 2) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir well at room temperature until the mixture is uniform. Then add 0.0316g of potassium nitrate to the solution and continue stirring for half an hour. Transfer the mixture to a steel jacket and crystallize at 180°C for 40h.
[0130] 4) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0131] 5) 0.3 g of catalyst precursor was loaded into a quartz tube, and first reduced with H2, with specific reduction conditions of 550°C, gas velocity of 10000 mL / (g·h), and reduction time of 2 h. After the reduction, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to raw gas C2H6 / N2=3 / 7, with a gas velocity of 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, with a reaction pressure of 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0132] Example 9
[0133] 1) Weigh 0.0784 g of anhydrous gallium nitrate, dissolve it in deionized water, and stir to fully dissolve it to obtain a white gallium salt solution; weigh 3 g of high-purity silica gel, drop the gallium salt solution on the high-purity silica gel, stir to fully impregnate it, then vacuum evacuate for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a Ga / SiO2 precursor;
[0134] 2) Weigh 0.0641 g of chloroplatinic acid, dissolve it in deionized water, stir to fully dissolve it, and obtain a yellow, clear and transparent platinum salt solution; add the platinum salt solution dropwise to the Ga / SiO2 precursor obtained in step 1), stir to fully impregnate it, then vacuum pump for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a GaPt / SiO2 precursor;
[0135] 3) Weigh 20.0591g of deionized water, grind the GaPt / SiO2 precursor obtained in step 2) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir well at room temperature until the mixture is uniform. Then add 0.0316g of potassium nitrate to the solution and continue stirring for half an hour. Transfer the mixture to a steel sleeve and crystallize at 180°C for 40h.
[0136] 4) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0137] 5) 0.3 g of catalyst precursor was loaded into a quartz tube, and first reduced with H2, with specific reduction conditions of 550°C, gas velocity of 10000 mL / (g·h), and reduction time of 2 h. After the reduction, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to raw gas C2H6 / N2=3 / 7, with a gas velocity of 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, with a reaction pressure of 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0138] Example 10
[0139] 1) Weigh 0.0406 stannous chloride dihydrate, dissolve it in deionized water, stir to fully dissolve it, and obtain a white tin salt solution; weigh 3g high-purity silica gel, drop the tin salt solution on the high-purity silica gel, stir to fully impregnate it, then vacuum evacuate for 1h, dry (120℃ / 12h), and calcine (400 / 2h) to obtain a Sn / SiO2 precursor;
[0140] 2) Weigh 0.0641 g of chloroplatinic acid, dissolve it in deionized water, stir to fully dissolve it, and obtain a yellow, clear and transparent platinum salt solution; add the platinum salt solution dropwise to the Sn / SiO2 precursor obtained in step 1), stir to fully impregnate it, then vacuum pump for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a SnPt / SiO2 precursor;
[0141] 3) Weigh 20.0591g of deionized water, grind the SnPt / SiO2 precursor obtained in step 2) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir well at room temperature until the mixture is uniform. Then add 0.0316g of potassium nitrate to the solution and continue stirring for half an hour. Transfer the mixture to a steel jacket and crystallize at 180°C for 40h.
[0142] 4) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0143] 5) 0.3 g of catalyst precursor was loaded into a quartz tube, and first reduced with H2, with specific reduction conditions of 550°C, gas velocity of 10000 mL / (g·h), and reduction time of 2 h. After the reduction, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to raw gas C2H6 / N2=3 / 7, with a gas velocity of 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, with a reaction pressure of 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0144] Embodiment 11
[0145] 1) Weigh 0.0560 g of indium nitrate, dissolve it in deionized water, stir it to fully dissolve, and obtain a colorless indium salt solution; weigh 3 g of high-purity silica gel, drop the indium salt solution on the high-purity silica gel, stir it to fully impregnate it, then vacuum evacuate for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain In / SiO2 precursor;
[0146] 2) Weigh 0.0641 g of chloroplatinic acid, dissolve it in deionized water, stir to fully dissolve it, and obtain a yellow, clear and transparent platinum salt solution; add the platinum salt solution dropwise to the In / SiO2 precursor obtained in step 1), stir to fully impregnate it, then vacuum pump for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain an InPt / SiO2 precursor;
[0147] 3) Weigh 20.0591g of deionized water, grind the InPt / SiO2 precursor obtained in step 2) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir thoroughly at room temperature until the mixture is uniform. Then add 0.0316g of potassium nitrate to the solution and continue stirring for half an hour. Transfer the mixture to a steel sleeve and crystallize at 180°C for 40h.
[0148] 4) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0149] 5) 0.3 g of catalyst precursor was loaded into a quartz tube, and first reduced with H2, with specific reduction conditions of 550°C, gas velocity of 10000 mL / (g·h), and reduction time of 2 h. After the reduction, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to raw gas C2H6 / N2=3 / 7, with a gas velocity of 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, with a reaction pressure of 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0150] Example 12
[0151] The catalyst was prepared according to the method of Example 4, except that the crystallization time was changed from 40 h to 96 h. The catalytic reaction results are shown in Table 1.
[0152] Embodiment 13
[0153] The catalyst was prepared according to the method of Example 4, except that the crystallization time was changed from 40 h to 60 h. The catalytic reaction results are shown in Table 1.
[0154] Embodiment 14
[0155] The catalyst was prepared according to the method of Example 4, except that the crystallization time was changed from 40 hours to 30 hours. The catalytic reaction results are shown in Table 1.
[0156] Embodiment 15
[0157] The catalyst was prepared according to the method of Example 4, except that the crystallization time was changed from 40 hours to 20 hours. The catalytic reaction results are shown in Table 1.
[0158] Example 16
[0159] The catalyst was prepared according to the method of Example 4, except that the crystallization time was changed from 40 hours to 10 hours. The catalytic reaction results are shown in Table 1.
[0160] Embodiment 17
[0161] The catalyst was prepared according to the method of Example 4, except that the crystallization time was changed from 40 hours to 8 hours. The catalytic reaction results are shown in Table 1.
[0162] Comparative Example 1
[0163] 1) Weigh 0.0717g of zinc acetate dihydrate, dissolve it in deionized water, stir it to fully dissolve, and obtain a white solution; weigh 3g of high-purity silica gel, drop the Zn salt solution on the high-purity silica gel, stir it to fully impregnate it, and then vacuum it for 1h to allow the metal salt solution to better enter the pores of the high-purity silica gel. Place the obtained material in a drying oven at 120°C for 12h, and then calcine it in an air muffle furnace at 400°C for 2h to obtain a Zn / SiO2 precursor;
[0164] 2) Weigh 20.0591g of deionized water, grind the Zn / SiO2 precursor obtained in step 1) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir at room temperature for 6h. Then transfer the mixture into a steel jacket and crystallize at 180°C for 40h.
[0165] 3) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0166] 4) 0.3 g of catalyst precursor was loaded into a quartz tube and first reduced with H2. The specific reduction conditions were 550°C, a gas velocity of 10000 mL / (g·h), and a reduction time of 2 h. After the reduction was completed, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to the raw gas C2H6 / N2=3 / 7, the gas velocity was 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, and the reaction pressure was 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0167] Comparative Example 2
[0168] 1) Weigh 1.4673g of dinitrodiammine platinum nitrate solution, dissolve it in deionized water, stir to fully dissolve it, and obtain a colorless, clear and transparent solution; drop the Pt salt solution onto high-purity silica gel, stir to fully impregnate it, and then vacuum evacuate for 1 hour to allow the metal salt solution to better enter the pores of the high-purity silica gel. Place the obtained material in a drying oven at 120°C for 12 hours, and then calcine it in an air muffle furnace at 400°C for 2 hours to obtain a Pt / SiO2 precursor;
[0169] 2) Weigh 20.0591 g of deionized water, grind the Pt / SiO2 precursor obtained in step 1) to less than 100 mesh and mix with deionized water, then drop 18.4050 g of TPAOH (20 wt%). Stir at room temperature for 6 h. Then transfer the mixture into a steel jacket and crystallize at 180°C for 40 h.
[0170] 3) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0171] 4) 0.3 g of catalyst precursor was loaded into a quartz tube and first reduced with H2. The specific reduction conditions were 550°C, a gas velocity of 10000 mL / (g·h), and a reduction time of 2 h. After the reduction was completed, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to the raw gas C2H6 / N2=3 / 7, the gas velocity was 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, and the reaction pressure was 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0172] Comparative Example 3
[0173] 1) Weigh 0.0776g of anhydrous gallium nitrate, dissolve it in deionized water, stir it to fully dissolve, and obtain a white solution; weigh 3g of high-purity silica gel, drop the Ga salt solution on the high-purity silica gel, stir it to fully impregnate it, and then vacuum it for 1h to allow the metal salt solution to better enter the pores of the high-purity silica gel. Place the obtained material in a drying oven at 120°C for 12h, and then calcine it in an air muffle furnace at 400°C for 2h to obtain a Ga / SiO2 precursor;
[0174] 2) Weigh 20.0591g of deionized water, grind the Ga / SiO2 precursor obtained in step 1) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir at room temperature for 6h. Then transfer the mixture into a steel jacket and crystallize at 180°C for 40h.
[0175] 3) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0176] 4) 0.3 g of catalyst precursor was loaded into a quartz tube and first reduced with H2. The specific reduction conditions were 550°C, a gas velocity of 10000 mL / (g·h), and a reduction time of 2 h. After the reduction was completed, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to the raw gas C2H6 / N2=3 / 7, the gas velocity was 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, and the reaction pressure was 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0177] Comparative Example 4
[0178] 1) Weigh 0.0402g of stannous chloride dihydrate, dissolve it in deionized water, stir it to fully dissolve, and obtain a white solution; weigh 3g of high-purity silica gel, drop the Sn salt solution on the high-purity silica gel, stir it to fully impregnate it, and then vacuum it for 1h to allow the metal salt solution to better enter the pores of the high-purity silica gel. Place the obtained material in a drying oven at 120°C for 12h, and then calcine it in an air muffle furnace at 400°C for 2h to obtain a Sn / SiO2 precursor;
[0179] 2) Weigh 20.0591g of deionized water, grind the Sn / SiO2 precursor obtained in step 1) to less than 100 mesh and mix with deionized water, then drop 18.4050g of TPAOH (20wt%). Stir at room temperature for 6h. Then transfer the mixture into a steel jacket and crystallize at 180℃ for 40h.
[0180] 3) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0181] 4) 0.3 g of catalyst precursor was loaded into a quartz tube and first reduced with H2. The specific reduction conditions were 550°C, a gas velocity of 10000 mL / (g·h), and a reduction time of 2 h. After the reduction was completed, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to the raw gas C2H6 / N2=3 / 7, the gas velocity was 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, and the reaction pressure was 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0182] Comparative Example 5
[0183] 1) Weigh 0.0554g of indium nitrate, dissolve it in deionized water, stir it to fully dissolve, and obtain a colorless solution; weigh 3g of high-purity silica gel, drop the In salt solution on the high-purity silica gel, stir it to fully impregnate it, and then vacuum it for 1 hour to allow the metal salt solution to better enter the pores of the high-purity silica gel. Place the obtained material in a drying oven at 120°C for 12 hours, and then calcine it in an air muffle furnace at 400°C for 2 hours to obtain an In / SiO2 precursor;
[0184] 2) Weigh 20.0591 g of deionized water, grind the In / SiO2 precursor obtained in step 1) to less than 100 mesh and mix with deionized water, then drop 18.4050 g of TPAOH (20 wt%). Stir at room temperature for 6 h. Then transfer the mixture into a steel jacket and crystallize at 180°C for 40 h.
[0185] 3) After crystallization is completed and cooled to room temperature, the catalyst is washed alternately with ethanol and water for 2-3 times until the pH of the filtrate is neutral. The catalyst is then dried (120°C / 12h) and calcined (550 / 6h) to burn off the template; then tableted at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0186] 4) 0.3 g of catalyst precursor was loaded into a quartz tube and first reduced with H2. The specific reduction conditions were 550°C, a gas velocity of 10000 mL / (g·h), and a reduction time of 2 h. After the reduction was completed, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to the raw gas C2H6 / N2=3 / 7, the gas velocity was 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, and the reaction pressure was 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0187] Comparative Example 6
[0188] 1) Weigh 3g of high-purity silica gel and grind it to less than 100 mesh. Weigh 20.0591g of deionized water, mix the ground powder with deionized water, and then drop 18.4050g of TPAOH (20wt%). Stir at room temperature for 6h. Then transfer the mixed solution to a steel jacket and crystallize at 180℃ for 40h to obtain pure silicon molecular sieve S-1.
[0189] 2) Weigh 1.4673 g of dinitrosodiammineplatinum nitric acid solution into a beaker, add 10 g of deionized water, then add the prepared S-1 molecular sieve, and stir at 60° C. under a magnetic stirrer until the water evaporates.
[0190] 3) The stirred material is dried in a drying oven (120°C / 12h), and then calcined in a muffle furnace (400°C / 2h); then tableted at 25MPa, and then granulated into 20-40 mesh to obtain a catalyst precursor.
[0191] 4) 0.3 g of catalyst precursor was loaded into a quartz tube and first reduced with H2. The specific reduction conditions were 550°C, a gas velocity of 10000 mL / (g·h), and a reduction time of 2 h. After the reduction was completed, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to the raw gas C2H6 / N2=3 / 7, the gas velocity was 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, and the reaction pressure was 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0192] Comparative Example 7
[0193] 1) Weigh 1.4673g of dinitrodiammine platinum nitrate solution, dissolve it in deionized water, stir to fully dissolve it, and obtain a colorless, clear and transparent solution; drop the Pt salt solution on the high-purity silica gel, stir to fully impregnate it, and then vacuum evacuate for 1 hour to allow the metal salt solution to better enter the pores of the high-purity silica gel. The obtained material is placed in a drying oven and dried at 120°C for 12 hours, and then calcined at 400°C in an air muffle furnace for 2 hours; then pressed into tablets at 25MPa, and then granulated to 20-40 mesh to obtain a catalyst precursor.
[0194] 2) 0.3 g of catalyst precursor was loaded into a quartz tube and first reduced with H2. The specific reduction conditions were 550°C, a gas velocity of 10000 mL / (g·h), and a reduction time of 2 h. After the reduction was completed, nitrogen was purged for half an hour, then the temperature was raised to 400°C and switched to the raw gas C2H6 / N2=3 / 7, the gas velocity was 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, and the reaction pressure was 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0195] Comparative Example 8
[0196] 1) Weigh 0.0717 g of zinc acetate dihydrate, dissolve it in deionized water, and stir it to fully dissolve it to obtain a white zinc salt solution; weigh 3 g of high-purity silica gel, drop the zinc salt solution on the high-purity silica gel, stir it to fully impregnate it, then vacuum evacuate for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain a Zn / SiO2 precursor;
[0197] 2) Weigh 1.4777 g of dinitrosodiammineplatinum nitrate solution, dissolve it in deionized water, stir to fully dissolve it, and obtain a colorless, clear and transparent platinum salt solution; add the platinum salt solution dropwise to the Zn / SiO2 precursor obtained in step 1), stir to fully impregnate it, then vacuum evacuate for 1 hour, dry (120°C / 12 hours), and calcine (400 / 2 hours) to obtain ZnPt / SiO2; then press it into tablets at 25 MPa, and then granulate it into 20-40 mesh to obtain a catalyst.
[0198] 3) 0.3 g of catalyst was loaded into a quartz tube, and H2 was used for reduction. The specific reduction conditions were 550°C, a gas velocity of 10000 mL / (g·h), and a reduction time of 2 h. After the reduction was completed, nitrogen was purged for half an hour, and then the temperature was raised to 400°C and switched to the raw gas C2H6 / N2=3 / 7, with a gas velocity of 2400 mL / (g·h), and the temperature was raised to 550°C for reaction, and the reaction pressure was 0.1 MPa. The catalytic reaction results are shown in Table 1.
[0199] Table 1
[0200]
[0201] From the results in Table 1, it can be seen that the catalysts prepared in Examples 1-17 by using the bimetallic embedded pure silicon molecular sieve catalyst prepared by the precursor-post-hydrothermal crystallization of the present invention have higher catalytic activity and higher ethylene selectivity.
[0202] Figure 1 is the X-ray diffraction pattern of the catalyst obtained in Examples 2, 4 and 6; Figure 1 It can be seen that Examples 2, 4, and 6 all obtained ZnPt@S-1 samples with MFI-type structures.
[0203] Figure 2a This is a SEM image of the ZnPt@S-1 molecular sieve catalyst obtained in Example 4; Figure 2b for Figure 2a A partial enlarged view of Figure 2a and Figure 2b It can be seen that the morphology of the ZnPt@S-1 molecular sieve catalyst of Example 4 presents a regular hexagonal prism shape and has a twin crystal structure of uniform size.
[0204] Figure 3 HRTEM image of the ZnPt@S-1 catalyst obtained in Example 4; Figure 3 It can be seen that the catalyst contains metal Pt and alloy Pt-Zn through the lattice spacing.
[0205] Figure 4a and 4b The particle size distribution diagrams of the ZnPt@S-1 catalyst obtained in Example 4 before and after the EDH (ethane catalytic dehydrogenation) reaction for 30 hours are shown respectively; Figure 4a and Figure 4b It can be seen that the particle size did not change before and after the EDH reaction, indicating that the catalyst has good anti-sintering performance and excellent stability.
[0206] Figure 5 The figure is a graph showing the change of ethane equilibrium conversion rate with temperature at 0.3 bar ethane partial pressure calculated using HSC 6.0 software. The ZnPt@S-1 catalyst obtained in Example 4 was used to carry out EDH (ethane catalytic dehydrogenation) reaction. Figure 5 It can be seen that under the conditions of 550°C and 30% ethane feed gas, the maximum equilibrium limit of ethane conversion is 15.7%, which indicates that this embodiment has achieved the maximum thermodynamic equilibrium conversion value of ethane under the reaction conditions, indicating that the catalyst has super high activity.
[0207] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An embedded catalyst, characterized in that: The embedded catalyst comprises a carrier and a main active component Pt and an optional auxiliary active component M embedded in the carrier; wherein the carrier is a pure silicon molecular sieve; and the auxiliary active component M is selected from one or more of Zn, Ga, Sn, In and K.
2. The embedded catalyst according to claim 1, wherein The molar ratio of the auxiliary active component M to the main active component Pt is 0.2-9:1, preferably 0.3-3.6:
1.
3. The embedded catalyst according to claim 1 or 2, wherein: In the embedded catalyst, based on the total weight of the embedded catalyst, the content of the main active component Pt is 0.5-1.5wt%, preferably 0.8-1.2wt%; the content of the auxiliary active component M is 0-1.5wt%, preferably 0.7-1.2wt%.
4. The embedded catalyst according to any one of claims 1 to 3, wherein: The pure silicon molecule is sieved from Silicalite-1 molecular sieve or β molecular sieve; And / or, the pore size of the pure silicon molecular sieve is 4.5-5.5 angstroms, and the specific surface area is not less than 300m 2 / g; And / or, the pure silicon molecular sieve has a regular hexagonal prism shape and a twinned crystal structure.
5. A method for preparing an embedded catalyst, characterized in that: The preparation method comprises: (1) impregnating a silicon source with a solution of a first metal salt, and subjecting the mixture to vacuum evacuation, drying and calcination to obtain a first catalyst precursor; (2) impregnating the first catalyst precursor with a solution of a second metal salt, and subjecting the mixture to vacuum evacuation, drying and calcination to obtain a second catalyst precursor; (3) hydrothermally crystallizing the second catalyst precursor in the presence of deionized water and a template, filtering, drying and calcining to obtain a catalyst precursor; (4) reducing the catalyst precursor in a reducing gas atmosphere to obtain an embedded catalyst.
6. The preparation method according to claim 5, wherein: The first metal salt is selected from one or more of zinc acetate dihydrate, zinc nitrate, tin nitrate, tin chloride, gallium nitrate, indium nitrate, potassium nitrate and potassium hydroxide; and / or, the second metal salt is selected from one or more of dinitrosodiammineplatinum, chloroplatinic acid and tetraammineplatinum nitrate; and / or, the mass ratio of the first metal salt to the silicon source is 0-1.5:1; and / or, the mass ratio of the second metal salt to the silicon source is 0.5-1.5:1; and / or, the molar ratio of deionized water, template agent and silicon source is 20-60:0.15-0.6:1; And / or, the drying conditions include: drying temperature 80-160° C., drying time 8-24 h; And / or, the calcination conditions include: calcination temperature 350-600° C., calcination time 1-8 h; And / or, the conditions of the hydrothermal crystallization include: a crystallization temperature of 170-200° C., a crystallization time of 8-96 h, preferably 8-60 h, more preferably 10-40 h; And / or, the reduction conditions include: reduction temperature 350-600° C., reduction time 1-3 h; And / or, the reducing gas is an inert gas containing hydrogen, wherein the volume content of hydrogen is 5-95%, and the gas velocity of the reducing gas is 20-60 mL / min.
7. The preparation method according to claim 5 or 6, wherein: The silicon source is selected from one or more of crystalline silicon dioxide, amorphous silicon dioxide and silicon dioxide gel colloid; And / or, the template agent is selected from tetrapropylammonium hydroxide, tetrapropylammonium bromide or tetraethylammonium hydroxide.
8. Use of the embedded catalyst according to any one of claims 1 to 4 or the embedded catalyst prepared by the preparation method according to any one of claims 5 to 7 in ethane dehydrogenation.
9. A method for dehydrogenating ethane, characterized in that: The method comprises: contacting a gas containing ethane with a catalyst to react and dehydrogenate ethane; Wherein, the catalyst is selected from at least one of the embedded catalysts described in any one of claims 1-4 or the embedded catalysts prepared by the preparation method described in any one of claims 5-7.
10. The method according to claim 9, wherein: The flow rate of the ethane-containing gas is 5-50 mL / min; And / or, the volume content of ethane in the ethane-containing gas is 5-90%; And / or, the reaction conditions are: reaction temperature is 450-650° C.; reaction pressure is 0.1-0.3 MPa.
Citation Information
Patent Citations
Catalyst and preparation method and application thereof
CN110479353A
Preparation method of ethane / propane conversion catalyst capable of working stably
CN110871106A
Cited By
Preparation method and application of platinum-based ethane oxidative dehydrogenation catalyst
CN120079400A
Cross-pore-rich Co-Silicalite-1 catalyst as well as preparation method and application thereof
CN121490810A